EMPLOYING TECHNOLOGICAL SUPPORT TO IMPROVE SMES LOGISTIC PERFORMANCE: A CASE STUDY ON THE GRAVITY LOCATION MODELS APPROACH FOR SMES IN INDONESIA - Fourry Handoko (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2022)
PT. YY, a business organization and an SME (Small to Medium Enterprise), is a distributor of Stick Jelly in FC and NJ branded packaging. Its distribution covers the Greater Malang area, Indonesia. This company often encounters logistical problems, that is delivery delays. Despite having made a delivery target and schedule based on the number of each customer’s requests, its vast marketing area often results in non-punctual delivery time. PT. YY is located too far from its customers, thus, it complicates the daily distribution flow. This study attempts to solve this problem by providing technological support to determine the appropriate location for its buffer warehouse/branch. The Gravity Location Models Approach is used by knowing each customer’s coordinates, the number of requests, and shipping costs. With this approach, the right coordinate point is obtained for establishing a subsidiary branch. Based on the results of calculations and simulations, as well as the location of the buffer, it was found that there was a shipping time saving and an increase in the distribution process efficiency value up to 48%.